PHARMACEUTICAL PREPARATION OF LAUHA BHASMA - Kumar Dash, *Manoj; Joshi, Namrata (International Journal of Ayurveda and Pharma Research, 2019)
In the present research paper, the pharmaceutical preparation of Lauha bhasma (calcined iron) is being presented. The various procedures adopted in the preparation of Lauha bhasma includes Samanya Shodhana (common purification process for iron) and Vishesha Shodhana (specific purification process for iron), Lauha marana by Bhanupaka (Heating of iron under sunrays) Sthalipaka (Heating of iron in a vessel) and Puta paka (Incineration of iron). Lauha was finally subjected to the process of Amriikaran (nectarization). The process of Puta paka was undergone in electric muffle furnace (EMF) and was repeated for sixty times each under identical conditions, at the temperature of 7500 C till 35th Puta and thereafter at 7000 C till the end of the Marana process i.e. 60 Puta. During the processing of iron, Triphala kwatha (decoction of three myrobalan) has been used as liquid media for Vishesha Shodhana, Bhanupaka, Sthalipaka and Puta paka. The study showed an increase in weight of Lauha after Bhanupaka and Stahlipaka i.e.,, 216% and 105.3%, respectively. It may be due to addition of solid content of Triphala kwatha. After Puta paka, 63%weight gain was observed in final product which may be attributed to addition of ash from Triphala kwatha. The Bhasma obtained fulfils all criteria and was found safe for oral administration.